2020
DOI: 10.31744/einstein_journal/2020ao5395
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of palliative sedation in the State of São Paulo: an emerging medical demand

Abstract: Objective: To investigate the prevalence of palliative sedation use and related factors. Methods: An observational study based on data collected via electronic questionnaire comprising 23 close-ended questions and sent to physicians living and working in the state of São Paulo. Demographic data, prevalence and frequency of palliative sedation use, participant's familiarity with the practice and related motivating factors were analyzed. In order to minimize memory bias, questions addressing use frequency and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A systematic review of studies which addressed ethical questions on end-of-life care of critically ill patients (Spoljar et al, 2020) as well as other systematic reviews of studies of patients who received palliative sedation have consistently demonstrated that palliative sedation does not hasten death (Maltoni et al, 2012; Beller et al, 2015). Despite those findings, many clinicians still have their concerns on palliative sedation (Benítez-Rosario and Ascanio-León, 2020; Piedade et al, 2020; Rodrigues et al, 2020) and relatives’ opinion may still be a barrier to implementing palliative sedation (Spineli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of studies which addressed ethical questions on end-of-life care of critically ill patients (Spoljar et al, 2020) as well as other systematic reviews of studies of patients who received palliative sedation have consistently demonstrated that palliative sedation does not hasten death (Maltoni et al, 2012; Beller et al, 2015). Despite those findings, many clinicians still have their concerns on palliative sedation (Benítez-Rosario and Ascanio-León, 2020; Piedade et al, 2020; Rodrigues et al, 2020) and relatives’ opinion may still be a barrier to implementing palliative sedation (Spineli et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being recommended by diverse guidelines (Cherny, 2014; Abarshi et al, 2017) and being reported as an important component in end-of-life care by diverse healthcare providers (Piedade et al, 2020; Rodrigues et al, 2020), there is still controversy on ethical aspects as well as comfort or distress associated with palliative sedation use (Voeuk et al, 2017; Benítez-Rosario and Ascanio-León, 2020). It has been widely known that cultural aspects influence end-of-life care (Sprung et al, 2019) and the same seems to be true for palliative sedation (Rodrigues et al, 2020), which seems to be less used in low- and middle-income countries compared with high-income countries (Arantzamendi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the original inscription event of the polychrome portrait, the cry comes from the words that dwell in the surface of silence, expressing themselves as the long-held wailing, the whispers and the empathy that characterise the use of one's voice among the women in Panmela Castro's atelier. Their conversation and their workshops often become the occasion to break long silences, producing and circulating narratives of counter-disavowal: they are 'soroconfessions', that is, dialogues negotiated and held in circumstances of pain and sorority or, as the women of the network would have it, dororidade (Piedade, 2017).…”
Section: The Eloquence Of Silencementioning
confidence: 99%
“…Currently, PST is considered one of the most important components of end-of-life care,8 9 but its ethics have been a topic of discussion 10. For example, how do we identify patients who need early palliative sedation?…”
Section: Introductionmentioning
confidence: 99%
“…4 5 Palliative sedation therapy (PST) is defined as an intervention that aims to alleviate intolerable suffering resulting from one or a combination of symptoms. [6][7][8][9] The European Association for Palliative Care (EAPC) defines PST as 'palliative sedation in the context of palliative medicine is the monitored use of medications intended to induce a state of decreased or absent unconsciousness to relieve the burden of otherwise intractable suffering in a manner that is ethically acceptable to the patient, family and healthcare providers'. 7 Furthermore, palliative sedation can be light or deep, as well as intermittent or continuous.…”
Section: Introductionmentioning
confidence: 99%